The impact of tourism activity and some macroeconomic variables on economic growth in the kurdistan region of iraq: standard analytical study for the period 2007-2013 - Khamy Nasir Rasheed; Shvann Atheer Mohamed Said (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The Kurdistan Region of Iraq possesses a large variety of tourism constituents that help creating fertile environment for tourism, to determine the impact of tourism activity on the economy of the Kurdistan Region for the period (2007-2013). The study utilised the descriptive analysis method for the tourism supply side, represented by the number of hotels, restaurants, and tourism villages; whereas, the tourism demand side represented by the number of tourists. Moreover, on one hand, It was found that there is a compatibility between the tourist supply and the tourist demand, and on the other hand for the purpose of employing the quantitative approach, the annual data were converted into quarterly data, and the findings of statistical and econometric tests exhibited a positive impact of the tourism activity represented by tourism revenuesin economic growth, and the existence of a long-term equilibrium relationship between the variables. Additionally, since the statistical value of the test (Jarque-Ber) at 5% significance level is smaller than that of the chi-square this means that the residuals of the model follow a natural distribution. Furthermore, working on increasing the volume of investments in the tourism sector and creating an appropriate and stable investment environment to ensure the contribution of the local and foreign investor in the sector are crucial. Tourism from an economic perspective is a productive sector and a source of financing for the national economy.